Penerapan Strategi Pembelajaran Inkuiri untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Keanekaragaman Hayati di Kelas X SMA Negeri 2 Tondano - Christin Natalia Tutainon; Anatje Lihiang; Femmy R. Kawuwung (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to improve students' learning outcomes on biodiversity materials by applying inquiry learning strategies in class X-A SMA Negeri 2 Tondano. This research was carried out in two cycles, each with three meetings. In the first cycle, the student's learning outcomes showed classical completeness only reached 50%, with an average score of 75.6. This is due to students' lack of active participation in passive learning. Based on the reflection results, improvements were made in the second cycle by emphasizing increasing students' activeness in asking, answering, and discussing. The results in the second cycle showed a significant improvement, with an average score of 86.6 and classical completeness reaching 90%. This improvement shows that inquiry learning strategies effectively improve student learning outcomes. Although two students had not achieved completeness, the remedial provided succeeded in helping them achieve results on par with other students. This research proves that inquiry-based learning can increase students' involvement in learning and improve their learning outcomes. Therefore, it is recommended that inquiry learning strategies be applied more widely in other classes to improve the quality of education.